The occurrence of metacercariae of Petasiger (Digenea: Echinostomatidae) in an unusual site, within the lateral line scales of cyprinid fishes - Molnar, Kalman; Gibson, David I; Cech, Gabor; Papp, Melitta; Deak-Paulus, Petra; Juhasz, Lajos; Toth, Norbert; Szekely, Csaba (Folia parasitologica, 2015)
During a regular veterinary inspection of fishes from Lake Balaton, Hungary, echinostomatid metacercariae (Digenea), with collar spines characteristic of species of the genera Petasiger Dietz, 1909 and Paryphostomum Dietz, 1909, were found in the lateral line scales of a roach Rutilus rutilus (Linnaeus), an apparently unique site. In a subsequent examination of 586 fishes from 20 different species, similar infections were found in 11 species. The infection was virtually restricted to the lateral line scales, other scales being infected only incidentally. These encysted metacercariae had 27 collar spines, including eight larger angle spines and 19 smaller dorsal spines arranged in two rows. Two types of metacercarial cyst were found. One type had a cyst diameter of 138-171 µm × 105-120 µm and three central dorsal spines that were larger than the remainder and tended to resemble the angle spines. The second type of metacercarial cyst had a diameter of 128-157 µm × 105-115 µm and all 19 dorsal spines of the metacercaria were of a similar size. ITS sequences of the second type of metacercaria exhibited a 100% similarity to sequences of two adult Petasiger phalacrocoracis (Yamaguti, 1939) specimens collected from the gut of Phalacrocorax carbo (Linnaeus) in Hungary and to P. phalacrocoracis deposited in the GenBank database. Sequences obtained from two metacercariae of the first type showed a 2.8-2.9 % difference from sequences of the second type of metacercaria and from those of adult specimens of P. phalacrocoracis from cormorants. Based on these results, the second type metacercaria is considered to be a larval stage of P. phalacrocoracis, but the identity of the first type is uncertain. The unusual location of these metacercariae in the lateral line scales is discussed in relation to their transmission.
Keywords: metacercaria; Cyprinidae; molecular identification; Kis-Balaton Reservoir; Lake Balaton